Evaluation of protein and lipid on feed of Tilapia Oreochromis niloticus - Niagara, Niagara; Muhammad Agus Suprayudi; Setiawati, Mia; Achmad Fauzi, Ichsan (Indonesian Society of Scientific Aquaculture (ISSA), 2025)
The goal of this study was to discover the optimal protein and lipid levels for increasing the growth performance of Nile tilapia Oreochromis niloticus. A 2×2 randomized factorial design was used for this research, and two treatment factors were used: the protein level (28% and 32%) and the lipid level (6% and 8%). So, there were four test treatments and carried out with three replications. Nile tilapia with an average body weight of 5.60 ± 0.06 g were grown in a 900×45×35 cm3 aquarium at a density of 20 fish/aquarium. The experimental fish were grown for 60 days and fed three times daily until they appeared to be satisfied. Parameters evaluated in this study were growth performance and blood chemistry. The fish fed with diet 32;8 showed significantly higher growth than other treatments. Plasma protein in the fish fed with 32;6 diets were higher than those of plasma triglycerides, high density lipoprotein, and low density lipoprotein content were the same among the treatments. The result shows that feed 28;8 has the best protein efficiency ratio and protein retention. Keywords: Oreochromis niloticus, protein sparing effect, lipid, feed ABSTRAK Tujuan penelitian ini adalah untuk mengetahui kadar protein dan lipid yang optimum dalam meningkatkan kinerja pertumbuhan ikan nila Oreochromis niloticus. Penelitian ini menggunakan rancangan acak faktorial 2×2 dengan dua faktor perlakuan yaitu kadar protein (28% dan 32%) dan kadar lipid (6% dan 8%). Jadi terdapat empat perlakuan uji dan dilakukan dengan tiga kali ulangan. Ikan nila dengan rata-rata bobot badan 5,60 ± 0,06 g dipelihara dalam akuarium berukuran 900×45×35 cm3 dengan kepadatan 20 ekor/akuarium. Ikan dipelihara selama 60 hari dan diberi makan tiga kali sehari secara at satiation. Parameter yang dievaluasi dalam penelitian ini adalah kinerja pertumbuhan dan kimia darah. Ikan yang diberi perlakuan dengan pakan 32;8 menunjukkan pertumbuhan yang lebih tinggi dibandingkan perlakuan lainnya. Protein plasma pada ikan yang diberi pakan 32;6 lebih tinggi dibandingkan dengan trigliserida plasma, HDL dan LDL rendah yang sama antar perlakuan. Hasil penelitian menunjukkan bahwa pakan 28;8 mempunyai nilai protein efesiensi rasio dan retensi protein terbaik. Kata Kunci: Oreochromis niloticus, protein sparing effect, lemak, pakan